The Influence of Psychosocial Factors on Motivation and Compliance in Table Tennis Training - Marpaung, Deni Rahman; Malau, Clarisa Anggriani; Napitupulu, Putri Anjeli; Ginting, Alan Gibron Ersada; Ginting, Inke Monica br (Journal Coaching Education Sports, 2024)
The aim of this research is to investigate the influence of psychosocial factors on motivation and compliance in table tennis training in Indonesia. The research method employed is a cross-sectional observational study involving 30 table tennis student participants from Medan State University. Data were collected through an online survey covering questions on motivation, social support, self-perception, motivation, and compliance in table tennis training. Data analysis involved descriptive analysis and regression to evaluate the relationships between these variables. The research results indicate that motivation, social support, and self-perception are significantly associated with athlete motivation and compliance. The implications of these findings underscore the need to consider psychosocial aspects in the development of training programs and athlete coaching in table tennis in Indonesia. However, this study has limitations and requires further research to validate these findings. Thus, this research provides valuable insights into understanding the factors influencing the performance of table tennis athletes in Indonesia and can serve as a basis for the development of more effective training strategies in the future.